Immunomodulation - hope for patient with Glioblastoma Multiforme - Litak, Jakub; Litak, Joanna; Czyżewski, Wojciech; Miziak, Paulina (Journal of Education, Health and Sport, 2018)
Glioblastoma multiforme is the most common and highly aggressive brain tumor, causing high number of death worldwide. Current therapies are not sufficient for patients. The surgical removal followed by radio- and chemotherapy became golden standard. Overall survival is still disappointing. New approach to GBM therapy is required . Immunotherapy seems to be a proper direction .